Modelling the effect of nonplanarity on charge transport along conjugated polymer chains - Correia, Helena M. G. (2007)
Conjugated polymers show interesting properties that make them appropriated for nanoelectronics. Several studies of poly(p-phenylene vinylene) (PPV) have suggested that each polymer chain consists of several planar segments, with conjugation length of nanoscale dimension, linked by twists or kinks. A pronounced twist between two planar segments in a PPV chain not only causes loss of main-chain conjugation but it may also alter electron and hole mobility along the chain, which has further implications for the percolation of charge through the polymer film. We used self-consistent quantum molecular dynamics calculations to provide information on the electric field needed to move the injected charges (either electrons or holes) along the planar segments of PPV and to cross the twist between two planar segments perpendicular to each other. Field-dependent charge mobility was also estimated for conjugated segments of various lengths. Our results suggest that electrons can cross the twist between adjacent planar segments for lower applied electric fields than holes if there is no more than one electronic charge (electron or hole) on the PPV chain, otherwise similar fields are needed.